Cell Therapy in Organ Transplantation: Our Experience on the Clinical Translation of Regulatory T Cells - Safinia, Niloufar; Grageda, Nathali; Scottà, Cristiano; Thirkell, Sarah; Fry, Laura J.; Vaikunthanathan, Trishan; Lechler, Robert I.; Lombardi, Giovanna (Frontiers in Immunology, 2018)
Solid organ transplantation is the treatment of choice for patients with end-stage organ dysfunction. Despite improvements in short term outcome, long term outcome is suboptimal due to the increased morbidity and mortality associated with the toxicity of immunosuppressive regimens and chronic rejection (1-5). As such, the attention of the transplant community has focused on the development of novel therapeutic strategies to achieve allograft tolerance, a state whereby the immune system of the recipient can be re-educated to accept the allograft, averting the need for long-term immunosuppression. Indeed, reports of ‘operational’ tolerance, whereby the recipient is off all immunosuppressive drugs and maintaining good graft function, is well documented in the literature for both liver and kidney transplantations (6-8). However, this phenomenon is rare and in the setting of liver transplantation has been shown to occur late after transplantation, with the majority of patients maintained on life-long immunosupression to prevent allograft rejection (9). As such, significant research has focused on immune regulation in the context of organ transplantation with regulatory T cells (Tregs) identified as cells holding considerable promise in this endeavour. This review will provide a brief introduction on human Tregs, their phenotypic and functional characterisation and focuses on our experience to date at the clinical translation of Treg immunotherapy in the setting of solid organ transplantation.